(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
This article presents the role of climatic factors in the formation of the fertility of irrigated meadow-alluvial soils in Bukhara region, as well as their levels and the dynamics of these factors over time. Accordingly, information is provided on how climate variability affects soil salinity levels and seasonal factors.